Profil Penderita Sinusitis Maksilaris di RSUD Abdoel Wahab Sjahranie Samarinda Tahun 2016-2020 - Virginia Uspa, Astria; Yani, Sinar; Sawitri, Endang (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2024)
Sinusitis is one of the health problems that has increased significantly and has an impact on people's financial expenditures. Sinusitis is an inflammation involving the nasal mucosa and paranasal sinuses. This study aimed to determine the characteristics of patients with maxillary sinusitis in RSUD Abdoel Wahab Sjahranie Samarinda in 2016-2020. This descriptive observational study used 142 secondary data in the form of patient medical record data. The results showed that 2 people 11 years old (1.4%), 12-25 years old as many as 30 people (21.1%), 26-45 years old as many as 61 people (43%), 46 years old as many as 49 people ( 34.5%). There were 86 women (60.6%), male as many as 56 people (39.4%). Not working as many as 60 people (42.3%), students as many as 18 people (12.7%), civil servants as many as 14 people (9.9%), private sector as many as 50 people (35.2%). Types of dentogen sinusitis as many as 86 people (60.6%), rhinogen as many as 56 people (39.4%). The main complaint was fever as many as 1 person (0.7%), mucopurulent discharge with a foul smelling as many as 103 people (72.5%), headache as many as 24 people (16.9%), tooth pain as many as 14 people (9.9% ). The right side affected as many as 48 people (33.8%), the left side affected as many as 59 people (41.5%), right and left sides were affected as many as 35 people (24.6%). It was concluded that maxillary sinusitis was mostly experienced by women aged 26-45 years old, did not work, the type was dentogen with the main complaint of mucopurulent discharge that had a foul odor and was most often affected on the left side.